PENGARUH MANAJEMEN SUMBER DAYA MANUSIA TERHADAP KINERJA GURU DI MI MIFTAHUL HUDA BANDULAN - Pujiharti, Endang Sih; Fauziyah, Ilmi (Sekolah Tinggi Ilmu Tarbiyah Togo Ambarsari, 2024)
Effective human resource management in educational institutions will have an impact on teacher performance. Teachers are a key factor in the success of the learning process, so that with good teacher performance it is hoped that educational goals will also be achieved well. The aim of this research is to determine the effect of human resource management on teacher performance at MI Miftahul Huda Bandulan. This research is quantitative correlational research. Data collection uses questionnaires and documentation. The data analysis technique uses the pearson product moment correlation test, coefficient of determination, and simple linear regression. The research results obtained an r value of 0.205 < 0.514 (???? calculated <????????????????le), which means there isn’t any significant relationship between human resource management and teacher performance. Then, in calculating the coefficient of determination in this research, it is 12%, meaning that the influence of human resource management on teacher performance is 12% and the remaining 88% is influenced by other factors. Meanwhile, in simple regression analysis, a significance value of 0.205 > 0.05 was obtained. This is confirmed by the calculated t result of -1.334, while the t table value is 2.16037 (t calculated < t table). So it can be concluded that Ho is accepted and Ha is rejected. In other words, there is no significant influence of human resource management variables on teacher performance variables at MI Miftahul Huda Bandulan.